Factors Causing Musculoskeletal Complaints in Batik Workers at Kraton District - Rifdah Wardani; Danisarah Prilly (Jurnal Info Sains : Informatika dan Sains, 2026)
Musculoskeletal disorders (MSDs) are a major occupational health problem worldwide. Batik workers are considered a high-risk group due to exposure to static work postures, repetitive movements, and long working hours. Purpose: This study aimed to identify the factors contributing to musculoskeletal complaints among batik workers in the Keraton district. Methods: A descriptive mixed-methods design was employed. Qualitative data were collected through in-depth interviews with three batik workers and analyzed using content analysis with the assistance of OpenCode software. Quantitative data were obtained through work posture observation using the Rapid Entire Body Assessment (REBA) method to assess ergonomic risk levels. Results: Interviews revealed complaints of pain in the shoulders, arms, knees, calves, thighs, ankles, neck, right elbow, waist, and back. Identified risk factors included age, duration of work, physical activity, overtime, and insufficient rest. REBA analysis showed scores of 7–9, indicating high risk requiring immediate intervention. Integration of qualitative and quantitative findings reinforced that batik activities impose repetitive strain on the musculoskeletal system.. Conclusion: Batik workers face a high risk of musculoskeletal disorders without adequate occupational health protection. Ergonomics-based interventions, occupational health education, and improvements in the work environment should be implemented promptly.